Analisis Fenomenologi Siswa terhadap Sistem Pembelajaran Hybrid Pascapandemi COVID-19 - Hardja, Diovanny; Sari, Wulan Purnama (Kiwari, 2025)
The Covid-19 pandemic has triggered drastic changes in the education system, including in skill-based vocational education such as culinary and pastry programs. The sudden shift to online learning, followed by the implementation of a hybrid model that combines online and offline methods, has created diverse learning experiences for students. This study explores the experiences of Culinary and Pastry students at the Tristar Institute regarding hybrid learning in the post-pandemic period. Using a qualitative approach, data were collected through in-depth interviews with selected students. The findings reveal that online learning was perceived as less suitable for practice-based courses, mainly due to limitations in live demonstrations, nonverbal interaction, and active student engagement. However, it was considered flexible and sufficient for delivering theoretical and informational content. The main challenges faced by students included technical issues such as unstable internet connections, lack of motivation, and the absence of a conducive study environment at home. This study concludes that hybrid learning, which combines online delivery for theory with offline sessions for practice, is essential for improving the quality of learning. It is recommended that educational institutions develop more adaptive and student-centered learning strategies and provide adequate technological support and training for both lecturers and students. Pandemi Covid-19 telah mendorong perubahan drastis dalam sistem pendidikan, termasuk pada pendidikan vokasi berbasis keterampilan seperti kuliner dan patiseri. Peralihan mendadak ke pembelajaran daring kemudian diikuti dengan penerapan model hybrid yang memadukan pembelajaran daring dan luring, menimbulkan beragam pengalaman belajar bagi mahasiswa. Penelitian ini mengeksplorasi pengalaman mahasiswa jurusan Kuliner dan Patiseri Tristar Institute terhadap pembelajaran hybrid pascapandemi Covid-19. Menggunakan pendekatan kualitatif, data dikumpulkan melalui wawancara mendalam dengan sejumlah mahasiswa. Hasil penelitian menunjukkan bahwa pembelajaran daring dinilai kurang optimal untuk mata kuliah berbasis praktik, terutama karena keterbatasan dalam demonstrasi langsung, interaksi nonverbal, dan keterlibatan aktif mahasiswa. Namun, pembelajaran daring dianggap fleksibel serta memadai dalam penyampaian materi teori yang bersifat informatif. Tantangan utama yang dihadapi mahasiswa meliputi kendala teknis, seperti koneksi internet yang tidak stabil, kurangnya motivasi belajar, serta keterbatasan ruang belajar yang kondusif di rumah. Kesimpulan penelitian ini menekankan pentingnya metode hybrid yang menggabungkan pembelajaran daring untuk teori dan pembelajaran luring untuk praktik guna meningkatkan mutu pembelajaran. Disarankan agar institusi pendidikan mengembangkan strategi pembelajaran yang lebih adaptif, responsif terhadap kebutuhan mahasiswa, dan menyediakan dukungan teknologi serta pelatihan yang memadai bagi dosen dan mahasiswa.